암 환자에서 한국어판 사기 저하 척도(DS-II-Kr)의 표준화 및 타당도 - 전민; 김선영; 김재민; 김성완; 신일선; 이주연; 이정재; 곽새롬; David W. Kissane (Singyŏng chŏngsin ŭihak, 2022)
Objectives Demoralization, which results from the inability to cope, is characterized by hopelessness, helplessness, and loss of the meaning and purpose of life. Although demoralization is prevalent in patients with chronic illness, including cancer, a Korean version of the scale has not been developed and validated. Thus, we translated into Korean and validated a version of the Demoralization Scale-II (DS-II-Kr) for cancer patients. Methods This cross-sectional study recruited cancer patients and survivors who visited a mental health clinic in a cancer hospital. Internal consistency, test-retest reliability, and concurrent validity of DS-II-Kr were assessed. Additionally, the construct validity of two sub-factors was evaluated using confirmatory factor analysis. The optimal DS-II-Kr cut-off point was determined by logistic regression analysis based on the distress cut-off in the Hospital Anxiety-Depression Scale (HADS). Results This study included 105 participants. The mean and standard deviation for total DS-IIKr scores were 11.9 and 7.6, respectively. The scale demonstrated good internal consistency and test-retest reliability. Goodness-of-fit analysis was moderate for the Meaning and Purpose subscale, and a good fit was found for the Distress and Coping Ability subscale. The DS-II-Kr cut-off value based on HADS was 10 (≤10 vs. >10). Conclusion The DS-II-Kr is a useful tool for assessing demoralization in clinical and research settings. However, further studies are needed to confirm the optimal DS-II-Kr cut-off score. External validation in other populations is also needed. KCI Citation Count: 0